Recovery of State Financial Losses as a Strategy for Combating Corruption Crimes: A Reform of Criminal Law - KMS Herman; K. Johnson Rajagukguk (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
Corruption constitutes a grave legal and societal issue, leading to the misallocation of public funds and adversely impacting critical sectors such as education, health, and infrastructure due to inadequate financial support. As an act of abuse of power for personal gain, corruption not only inflicts significant financial losses on the state but also undermines the stability of social, economic, and governance frameworks. In the Indonesian context, the eradication of corruption demands heightened attention, as the financial detriment suffered by the state due to corrupt practices frequently reaches substantial amounts. Anti-corruption efforts prioritize not merely the imposition of sanctions on offenders but also the restitution of state financial losses. Such restitution is a pivotal mechanism for reinstating the rights of the state and the public, serving as a prospective solution for strengthening anti-corruption measures within the framework of criminal law reform in Indonesia. From an Islamic criminal law perspective, the restitution of state financial losses aligns with key principles of justice ('adl), accountability (mas'uliyyah), and the prohibition of harm (darar). Islamic law advocates for the recovery of misappropriated assets as an ethical and legal obligation to restore societal balance and prevent future misconduct. This study concludes that integrating Islamic principles into Indonesia's criminal law framework can enhance the effectiveness of corruption eradication efforts. The synergy between conventional legal mechanisms and Islamic criminal law offers a comprehensive approach to ensuring accountability, promoting justice, and safeguarding public resources.